(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
History of development and improvement of tandem mass spectrometry, possibilities of its application at the contemporary stage in various fields of medicine and biotechnology including production of novel medicinal preparations, identification of biologically active substances, pathogenic microorganisms and causative agents of especially dangerous infections is given.